Bottom-up design toward dynamically robust polyurethane elastomers. (18th March 2021) - Hsieh, Alex J.; Mason Wu, You-Chi; Hu, Weiguo; Mikhail, John P.; Veysset, David; Kooi, Steven E.; Nelson, Keith A.; Rutledge, Gregory C.; Swager, Timothy M.
Abstract: Segmented polyurethanes exhibit versatile mechanical properties, where their outstanding resilience and toughness enable material designs with high energy-absorption capability. However, there is a lack of fundamental understanding regarding the underlying molecular pathways toward rapid dissipation of high-pressure fields. Here, we design a set of 4, 4′-methylenediphenyldiisocyanate (MDI)−butanediol (BDO)−poly(tetramethylene oxide) (PTMO)-based polyurethanes and elucidate the influence of composition on thermal transition characteristics, crystallinity, segmental dynamics of PTMO, as well as high-strain-rate impact response on the microscale. Furthermore, simulations of shock compression, performed using an isotropic, constant-stress Hugoniostat method, comparing a MDI-BDO-PTMO-based polyurethane with polyethylene models of varying crystallinity suggest that the high-rate mechanical response is dominated by a soft domain response, which in turn can be sensitive to specific interactions present in the PTMO component that are not present in PE. Graphical abstract: Image 1 Highlights: MDI-PTMO and MDI-BDO-PTMO with PTMO MW of 2900 g/mol exhibit bimodal soft-segment melting endotherms. MDI-BDO-2900 (9:1) with 9:1 [BDO]:[PTMO] ratio exhibits a higher-Tm endotherm of the MDI-BDO hard domains. 13 C ssNMR reveals insights of the PTMO crystallinity and the corresponding molecular-level dynamics. Hugoniostat simulations highlight the shock behavior dominated by the response of soft domains. Enabling H-bond interactions raises the rigidity of PTMO also a plausible pathway for pressure-induced dynamic stiffening.